2007
DOI: 10.1080/10245330701521572
|View full text |Cite
|
Sign up to set email alerts
|

Once weekly recombinant human erythropoietin treatment for cancer-induced anemia in children with acute lymphoblastic leukemia receiving maintenance chemotherapy: A randomized case-controlled study

Abstract: Treatment with QW epoetin-alpha was found to increase Hb levels, decrease transfusion requirement, and improve functional status and QOL in anemic patients with ALL in maintenance receiving chemotherapy. The once-weekly schedule is convenient, safe, and may reduce the burden on patients, parents, and their caregivers by reducing the number of visits to the clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
14
0
1
Order By: Relevance
“…The treatment duration varies between 8 and 28 weeks. Despite the differences in dosage, treatment intervals, and duration for previous studies, a significant increase in Hb levels, a decrease in transfusion rates, and an improvement of QoL have been reported in all studies [9][10][11][12][13][14]. The effect of EPO has been found to be low, and transfusion rates are high in patients receiving platinumbased regimens; these results have been attributed to direct cytotoxic effects on renal cells and a decrease in EPO production.…”
Section: Discussionmentioning
confidence: 58%
“…The treatment duration varies between 8 and 28 weeks. Despite the differences in dosage, treatment intervals, and duration for previous studies, a significant increase in Hb levels, a decrease in transfusion rates, and an improvement of QoL have been reported in all studies [9][10][11][12][13][14]. The effect of EPO has been found to be low, and transfusion rates are high in patients receiving platinumbased regimens; these results have been attributed to direct cytotoxic effects on renal cells and a decrease in EPO production.…”
Section: Discussionmentioning
confidence: 58%
“…Front-loaded dosing has been shown to accelerate the hemoglobin response and reduce the need for transfusion [11]. Regular weekly dosing has shown marked efficiency in both adult and pediatric leukemia patients [3,4,10]. Extended dosing schedule (EDS) given every 3 weeks (Q3W) synchronously with chemotherapy cycles in adult patients appears to be similarly efficacious to weekly dosing [3,4,12].…”
Section: Discussionmentioning
confidence: 97%
“…Being a synthetic, chemically modified EPO analogue with a longer half-life and a slower rate of absorption compared to other ESAs [2,5,10], darbepoetin alfa was used in our patients as a single subcutaneous injection of 2.25 ug/kg. Almost 68.5% of our patients receiving darbepoetin required transfusion compared to 92% of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The largest of these trials found no difference overall, but a significant difference in a small subset of patients 5–7 years of age 3. Two much smaller trials of Abdelrazik and Fouda 8 and Csaki et al 11 claimed to show some benefit with the tools they used, but the number of patients in those trials totaled only 30 and 15, respectively, and the smaller one provided no statistical analysis of their findings.…”
Section: Quality Of Life Effectsmentioning
confidence: 98%